Antihepatitis B Virus Activity of a Protein-Enriched Fraction from Housefly (Musca domestica) in a Stable HBV-Producing Cell Line. (22nd June 2014) - Lu, Xuemei; Jin, Xiaobao; Wang, Jie; Chu, Fujiang; Zhu, Jiayong
Abstract : Hepatitis B virus (HBV) infection remains a major public health problem. Although several vaccines and therapeutic strategies are currently being implemented to combat HBV virus, effective antiviral therapy against HBV infection has not been fully developed. Alternative strategies and new drugs to combat this disease are urged. Insects and insect derivatives are a large and unexploited source of potentially useful compounds for modern medicine. In the present study, we investigated the first anti-HBV activity of a protein-enriched fraction (PE) from the larvae of the housefly ( Musca domestica ) in a stable HBV-producing cell line. HBsAg and HBeAg in the culture medium were measured by enzyme-linked immunosorbent assay. HBV-DNA was quantified by fluorescent quantification PCR. HBV core protein was assayed by immunofluorescent staining. Results indicate PE treatment inhibited both HBsAg, HBeAg secretion, and HBV-DNA replication. Furthermore, PE could also suppress HBV core protein expression. PE could be a potential candidate for the development of a novel and effective drug for the treatment of HBV infection.